Synopsis: Agricultural Mechanization in Rwanda - Takeshima, Hiroyuki; Benimana, Gilberthe Uwera; Spielman, David J.; Warner, James (International Food Policy Research Institute, 2024)
Optimal agricultural mechanization strategies in Rwanda can be better informed by a closer assessment of diverse production environments and experiences in other countries with similar topography. The findings from Rwanda’s latest agricultural surveys, review of recent experiences in countries with rugged terrain and smallholder farming systems similar to Rwanda and reviewing mechanization support strategies from other countries suggest that identifying mechanization technologies suitable for different types of farms, promoting greater private-sector innovations while focusing on the relevant public goods aspect of mechanization is the most promising way forward. Key findings include the following: • Variations in agroecology and cropping systems, irrigated/rainfed systems, farm size, and labor use intensity, among other factors, characterize the key types of mechanization use in Rwanda. • In the medium term, smallholders cultivating rainfed maize and legumes, in addition to irrigated rice, can benefit from the use of tractors, as well as irrigation pumps. • However, farm wages may still be too low and tractor-hiring fees may still be too high in Rwanda to induce a shift to mechanization in the short term. • Policy support for mechanization can focus on improving the understanding of mechanization needs among each type of farmers identified, knowledge of suitable machines, and required skills for their operations and maintenance. • Developing competitive markets and supply networks for promising machines, parts, and repair services at a viable and integrated market scale is also important.